INFLUENCE OF GRAPE SEED EXTRACT SOLUTION ON MICROLEAKAGE BETWEEN COMPOSITE RESIN AND DENTIN - Wardojo, Sonny Prasetyo; Meidyawati, Ratna; Usman, Munyati (International Journal of Applied Pharmaceutics, 2017)
Objectives: The purpose of this study is to evaluate the influence of grape seed extract (GSE) solution as dentin biomodification on microleakage between composite resin and dentin. Methods: A total of 52 dentin specimens were divided into two groups. Group 1 involved the application of GSE solution for 30 seconds after etching. Group 2 served as the control group. Results: The GSE solution group significantly increases microleakage between the composite resin and dentin compared to the control group. Conclusions: The application of GSE solution after etching can increase microleakage between composite resin and dentin.